Laryngeal and vocal alterations after thyroidectomy - Iyomasa, Renata Mizusaki; Tagliarini, José Vicente; Rodrigues, Sérgio Augusto; Tavares, Elaine Lara Mendes; Martins, Regina Helena Garcia (Elsevier, 2017)
Introduction: Dysphonia is a common symptom after thyroidectomy. Objective: To analyze the vocal symptoms, auditory-perceptual and acoustic vocal, videolaryngoscopy, the surgical procedures and histopathological findings in patients undergoing thyroidectomy. Methods: Prospective study. Patients submitted to thyroidectomy were evaluated as follows: anamnesis, laryngoscopy, and acoustic vocal assessments. Moments: pre-operative, 1st post (15 days), 2nd post (1 month), 3rd post (3 months), and 4th post (6 months). Results: Among the 151 patients (130 women; 21 men). Type of surgery: lobectomy + isthmectomy n = 40, total thyroidectomy n = 88, thyroidectomy + lymph node dissection n = 23. Vocal symptoms were reported by 42 patients in the 1st post (27.8%) decreasing to 7.2% after 6 months. In the acoustic analysis, f0 and APQ were decreased in women. Videolaryngoscopies showed that 144 patients (95.3%) had normal exams in the preoperative moment. Vocal fold palsies were diagnosed in 34 paralyzes at the 1st post, 32 recurrent laryngeal nerve (lobectomy + isthmectomy n = 6; total thyroidectomy n = 17; thyroidectomy + lymph node dissection n = 9) and 2 superior laryngeal nerve (lobectomy + isthmectomy n = 1; Total thyroidectomy + lymph node dissection n = 1). After 6 months, 10 patients persisted with paralysis of the recurrent laryngeal nerve (6.6%). Histopathology and correlation with vocal fold palsy: colloid nodular goiter (n = 76; palsy n = 13), thyroiditis (n = 8; palsy n = 0), and carcinoma (n = 67; palsy n = 21). Conclusion: Vocal symptoms, reported by 27.8% of the patients on the 1st post decreased to 7% in 6 months. In the acoustic analysis, f0 and APQ were decreased. Transient paralysis of the vocal folds secondary to recurrent and superior laryngeal nerve injury occurred in, respectively, 21% and 1.3% of the patients, decreasing to 6.6% and 0% after 6 months.
Keywords: Acoustic analysis; Dysphonia; Hoarseness; Laryngeal paralysis; Thyroidectomy